1996
DOI: 10.1002/anie.199612301
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Glycopeptides and Lipopeptides by Chemoselective Ligation

Abstract: Completely unprotected peptides carrying chemoselectively addressable groups react under very mild conditions with free reducing sugars or lipidic aldehydes to form glycopeptides or lipopeptides (for example the somatostatin analogue 1) of any desired structural complexity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
70
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(70 citation statements)
references
References 21 publications
0
70
0
Order By: Relevance
“…As a second illustrative example for the use of HCan building blocks in chemoselective ligation chemistry, a glycopeptide as a prototype for chimeric molecules [19] was prepared (Scheme 3. In analogy to the linear decapeptide above, the tetrapeptide HScheme 2 Synthesis of the cyclic decapeptide containing two Aloc-protected HCan residues showing the orthogonally addressable side chains.…”
Section: Hcan In Peptide Synthesismentioning
confidence: 99%
“…As a second illustrative example for the use of HCan building blocks in chemoselective ligation chemistry, a glycopeptide as a prototype for chimeric molecules [19] was prepared (Scheme 3. In analogy to the linear decapeptide above, the tetrapeptide HScheme 2 Synthesis of the cyclic decapeptide containing two Aloc-protected HCan residues showing the orthogonally addressable side chains.…”
Section: Hcan In Peptide Synthesismentioning
confidence: 99%
“…[15] It is also possible to link a peptide bearing an aminooxy function to the anomeric center of a free aldose in a chemoselective way, that is, without use of protecting groups. [16] It is well known that when using a reacting unit bearing a ™primary∫ À O À NH 2 group, an open-chain sugar oxime is obtained, [17] but it has also been observed that the cyclic form of the sugar is restored when a peptide with a ™secondary∫ hydroxylamino group (RÀOÀNHÀR') is used. [18] By following this last approach, if R and R' were sugar units, it would be possible in principle to obtain disaccharides and, more generally, oligosaccharide mimics by working in water and avoiding the use of any activation and protection strategy.…”
Section: Introductionmentioning
confidence: 99%
“…In early examples of this chemoselective reaction, sugars and peptides that contain secondary alkoxylamines were reacted with Dglucose, D-mannose, D-galactose, lactose, and N-acetyl-Dglucosamine to generate oligosaccharide and glycopeptide mimics, respectively (12,13). These pioneering studies revealed that, unlike primary alkoxylamines, which provide open-chain oxime isomers (14), secondary alkoxylamines react to form closed-ring neoglycosides (Fig. 1B).…”
mentioning
confidence: 99%